Civilize to consume: slums and civilizing processes in the documentary series No reservations (Comunicação & Inovação, 2016)
This article discusses the imaginaries aboutslums in the city of Rio de Janeiro in theAnthony Bourdain's travel documentary seriesNo reservations. Using a critical analysis, it ispossible to realize that the episode shows UPPsand opportunities in sports, specifically inBrazilian Jiu-Jitsu, as ways to achieve a more"worthy" and "desired" life - or, from anotherperspective, as civilizing processes, within acontext in which the slum becomes a productto be consumed, as a new tourist destination inthe "divided city".
Keywords: Imaginaries. City. Consumption.